25. PREDICTIVE VALUE OF LUNG AND DIAPHRAGM ULTRASOUND FOR WEANING FROM MECHANICAL VENTILATION IN SURGICAL ICU PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the predictive value of the lung ultrasound score, diaphragmatic excursion, and diaphragm thickening fraction for weaning outcomes in surgical intensive care unit patients.Methods: We conducted a prospective observational study of 74 postoperative adults who had received invasive mechanical ventilation for ≥ 48 hours and were eligible for weaning at the Center for Anesthesiology and Intensive Care, Hanoi Medical University Hospital. A spontaneous breathing trial was performed when standard readiness criteria were met. Lung and diaphragmatic ultrasonography were obtained at the beginning and end of the spontaneous breathing trial. Measured parameters included diaphragmatic excursion, diaphragm thickening fraction, and lung ultrasound score.Results: Of 74 patients, 54 patients (72.97%) were successfully weaned. Lung ultrasound score yielded the highest area under the receiver operating characteristic curve (AUC) at 0.94; a cut-off of 10 points provided 96% sensitivity and 80% specificity. Diaphragm thickening fraction showed an AUC of 0.91; a cut-off of 22.5% provided 87% sensitivity and 90% specificity. Diaphragmatic excursion had an AUC of 0.71; a cut-off of 11.7 mm provided 91% sensitivity and 47% specificity.Conclusions: In surgical intensive care unit patients, ultrasound-derived indices predict weaning outcomes. Lung ultrasound score and diaphragm thickening fraction demonstrated superior discriminative performance compared with diaphragmatic excursion.
Keywords: Lung ultrasound, diaphragm ultrasound, diaphragmatic excursion, diaphragm thickening fraction, mechanical ventilation weaning, postoperative intensive care, extubation prediction.